AN APPROACH ON THE THEMES OF WILLIAM SHAKESPEARE'S ROMEO JULIET - Agnes Emmie Kussemiarti; Ririn Sotyarini (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
“Romeo and Juliet” is one of the most prominent plays written by William Shakespeare. The play mostly narrates the binary of love and hate. It narrates the love between two main characters, Romeo and Juliet, as well as hate between two families named Capulet and Montague. This study aims to scrutinize the theme that is ultimately also the major concern in defining a play. This research is a library research that employs the theory of theme and structural analysis. The finding covers the intrinsic aspects of the play such as plot, setting, and characters that reflect the theme of the play. The themes of “Romeo and Juliet” are the love between Romeo and Juliet, the hate between two family, and also death. Romeo and Juliet are secretly getting married however their love becomes a tragedy when they have to overcome their family’s conflict. The plot presents a tragedy that is developed in the exposition, rising action, climax, resolution, and conclusion.